Evaluation of Drainage System Performance in Urban Areas at Risk of Flooding: A Case Study on Prima Street to Sungai Buun, West Kotawaringin Regency - Barus, Freddy; Sutarto, Tommy E.; Widiawati, Dhiana Dwi (Fakultas Teknik Universitas Brawijaya, 2025)
The flooding phenomenon in the Prima Street area is due to a lack of facilities, sub-optimal drainage channel conditions, bottlenecks, and elevation differences in the Box Culvert. The purpose of this study is to evaluate the storage capacity of the existing channel along Prima Street toward Sungai Buun and provide recommendations. The measurement results show that the elevation difference in the drainage channel with the Prima Street box culvert is ± 1.39 meters. The evaluation results show that the storage capacity of the existing channel on Prima Street (point 2) of 0.372 m³/s is smaller than the flood discharge of 0.490 m³/s. Flooding also often occurs in the channel behind Rocket Chicken (point 3) because the channel storage capacity is smaller than the flood discharge of 1.723 m³/s and 2.213 m³/s, respectively. There are three alternative solutions. The first alternative plans the drainage channel at point 2, with the base width (B) and top width of the channel (T) of 1.715 meters, channel depth (h) of 1.286 meters, normal depth of 0.857 meters, and accommodated discharge of 0.735 m³/s. Furthermore, the design flood discharge for a 5-year return period is 0.490 m³/s. The second alternative plans the drainage channel at point 3, cross section of the base width (B) and top width of the channel (T) 1.847 meters, channel depth (h) 1.386 meters, and normal depth at an elevation of 0.924 meters. The third alternative readjusts the base elevation of the Box Culvert to an elevation of ± 1.39 meters.